(untitled) (Journal of Environmental Science and Natural Resources, 2013)
This study deals with the investigation of water quality of the Buriganga river, Dhaka. For this purpose, samples were collected from five locations of the Buriganga river of Bangladesh during wet (monsoon) and dry (winter) season in 2011 to determine the spatial distribution and temporal variation of various water quality parameters. Water samples were collected from three different depths of river. The color was light brown in wet season and slightly black to black color in dry season. The water was found slightly acidic to slightly alkaline (6.6-7.5). Water temperature ranged from 18.2°C (dry) to 27.04°C (wet). The river was found to be highly turbid both in dry and wet season. Biochemical Oxygen Demand (BOD), Electric Conductivity (EC) and Total Dissolved Solids (TDS) were found higher in the dry season compared to that of wet season, while Dissolved Oxygen (DO) was found higher in wet season. The mean values of parameters were EC: wet- 1685 ?s/cm, dry-2250 ?s/cm; DO: wet- 4.9 mg/L, dry-3.7 mg/L; BOD: wet- 26.4 mg/L, dry- 33.4 mg/L; TDS: wet-238 mg/L, dry- 579 mg/L; transparency: wet- 24.6 cm, dry- 22.8 cm. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14600 J. Environ. Sci. & Natural Resources, 5(2): 47-52 2012